Heterogeneous treatment effects in groups - Gerhard Riener; Simon Wiederhold (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We show in a laboratory experiment that the same method of group induction carries different behavioral consequences. These heterogeneous treatment effects can be directly related to the quality of the relationship established between the subjects. Our results indicate the importance of manipulation checks in group-formation tasks in economic experiments.
Keywords: C92; M54; D03; J22; 330; Group induction; Control; Laboratory experiment; Manipulation check